The Application Of Data Analytics In The External Audit Activities Of Public Accounting Firms In Indonesia: The Levels Of Auditor Adoption And Perception - Yosua Aurelio; Muhammad Tojibussabirin (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study discusses the application of data analytics in the external audit activities carried out by one of the Big Four public accounting firms in Indonesia, EY Indonesia. The objective is to analyze how this technology enhances its efficiency and effectiveness in detecting frauds and data anomaly, including its adoption level among auditors, as well as to identify strategies to optimize the firm’s external audits and practices. This qualitative study uses primary data acquired from open questionnaires distributed to the firm’s external auditors as the respondents and secondary data form the firm’s published reports and official articles. The results of the analysis suggest that the adoption rate of data analytics in the external audit activities carried out by EY Indonesia has reached a significant level, providing various benefits in the process. The informants also agreed that data analytics improves audit efficiency, effectiveness, and quality. This technology enables work hour reduction, data analysis automation, and more accurate error and anomaly detections. In addition, the technology supports deeper analysis based on accurate data. However, this study also recognizes challenges such as the necessity of adapting the auditors’ skills in the mastery of the new technology and ensuring the completeness and accuracy of the analyzed data. The conclusion is that, although data analytics has positively contributed to external audit’s efficiency, effectiveness, and quality, further optimization is required, particularly through better trainings and infrastructure developments.